PRAKTIK BIDAN SEBAGAI PENDIDIK PADA PERAWATAN KEHAMILAN DI KABUPATEN MAGELANG - Siti Rofi'ah (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2016)
Background :Health education that is given by midwive in antenatal care was hoped can improve the knowledge, grow the attitude and positif behaviour from pregnant women to care her pregnancy and health.Objective : This research intents to analize the factors that related to the midwifery practice in carrying the rule as an educator at antenatal care. Method : This research is an explanatory research by using design cross sectional study with qualitative and quantitative approaches. The cuantitative research sample is 57 midwives, 5 pregnant women, 1 worker from health institution and IBI organization of Magelang district for checking the data.Result : The research results prove that most of the respondences (68,4 %) do the practice well. Factors that related to the midwifery practice in carrying the rules as an educator at antenatal care, are midwive attitude, period in midwive’s work and midwive community behaviour. And the most dominant factor that influence to midwivery practice in carrying the rule as an educator at antenatal care is midwive community behaviour